Detection of pesticides in food products using paper-based devices by UV-induced fluorescence spectroscopy combined with molecularly imprinted polymers - Vodova, Milada; Nejdl, Lukas; Pavelicova, Kristyna; Zemankova, Kristyna; Rrypar, Tomas; Skopalova Sterbova, Dagmar; Bezdekova, Jaroslava; Nuchtavorn, Nantana; Macka, Mirek; Adam, Vojtech; Vaculovicova, Marketa (Food chemistry, 2022)
In this proof-of-concept study, we explore the detection of pesticides in food using a combined power of sensitive UV-induced fingerprint spectroscopy with selective capture by molecularly imprinted polymers (MIPs) and portable cost-effective paper-based analytical devices (PADs). The specific pesticides used herein as model compounds (both pure substances and their application products for spraying), were: strobilurins (i.e. trifloxystrobin), urea pesticides (rimsulfuron), pyrethroids (cypermethrine) and aryloxyphenoxyproponic acid herbicides (Haloxyfop-methyl). Commercially available spraying formulations containing the selected pesticides were positively identified by MIP-PADs swabs of sprayed apple and tomato. The key properties of MIP layer - imprinting factor (IF) and selectivity factor (α) were characterized using trifloxystrobin (IF-3.5, α-4.4) was demonstrated as a potential option for in-field application. The presented method may provide effective help with in-field testing of food and reveal problems such as false product labelling.
Keywords: Pesticides; Fingerprint; Spectrometry, Fluorescence; Molecularly imprinted polymers; molekulárně imprintované polymery; Photochemistry; pesticidy; UV-induced fluorescence fingerprinting; molekulový imprinting; Molecular Imprinting; Molecularly Imprinted Polymers; fluorescenční spektrometrie